The study on the relationships among film fans' willingness to pay by film crowdfunding and their influencing factors. Issue 1 (1st January 2020) - Huang, Weilun
Abstract: The present study examined the relationship between film fans' willingness to pay by film crowdfunding (WPFC) and the incentives of film crowdfunding (FC) in China, which include material and non-material rewards. Moreover, this paper examined the mediating effects of film fans' perceived conveniences and risks of film crowdfunding platforms (FCPs) and the moderating effect of fans' individual characteristics such as gender, age, monthly income, monthly investment, and monthly expenditure on watching movie on the relationship between WPFC and incentives of FC. An online questionnaire was developed to investigate film fans in China, and 505 valid reports from film fans with a monthly expenditure for movies higher than zero were included in the data analysis. Structural equation modeling showed that most Chinese fans tend to sponsor projects published in FCPs, and their WPFC were affected by perceived values of non-material feedback but not by perceived values of material feedbacks. Moreover, film fans' perceived risks of FCP have significant mediating effects on the relationship between WPFC and incentives of FC, whereas their perceived convenience of FCP did not have a significant mediating effect. Furthermore, film fans' gender, age, monthly income, monthly investment, and monthly expenditure for watching movies had a moderating impact on these relationships.